2016
DOI: 10.1177/1524838016650187
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking and Health: A Systematic Review of Research Methods

Abstract: Trafficking in persons (TIP) is a human rights violation with serious public health consequences. Unfortunately, assessing TIP and its health sequelae rigorously and reliably is challenging due to TIP's clandestine nature, variation in definitions of TIP, and the need to use research methods that ensure studies are ethical and feasible. To help guide practice, policy, and research to assess TIP and health, we undertook a systematic literature review of 70 peer-reviewed, published articles to (a) identify TIP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 74 publications
1
20
1
Order By: Relevance
“…Findings of a bibliometric analysis are difficult to obtain by other research methods such as systematic or scoping reviews. For example, a recent systematic review of research methods on HT and health concluded that despite the presence of various quantitative and qualitative data collection and analysis methods, the implemented methodological approaches have limitations that affect what is known about HT and health [ 41 ]. Most available literature on HT is based on emotional stories rather than on empirical research [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of a bibliometric analysis are difficult to obtain by other research methods such as systematic or scoping reviews. For example, a recent systematic review of research methods on HT and health concluded that despite the presence of various quantitative and qualitative data collection and analysis methods, the implemented methodological approaches have limitations that affect what is known about HT and health [ 41 ]. Most available literature on HT is based on emotional stories rather than on empirical research [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the reason for being trafficked, an individual's development and life trajectory is negatively disrupted. Many may seek the support of mental health services, physical healthcare services, and social services (Cannon, Arcara, Graham, & Macy, 2016).…”
Section: The Health Needs Of Trafficked Personsmentioning
confidence: 99%
“…Relative to other problems such as intimate partner violence, anti-trafficking practicepolicy feedback loops, in which health care professionals and researchers inform the work of policymakers, are in their infancy. While some researchers have developed and tested appropriate screening tools, little research exists on the evaluation and development of evidence-based practices for identifying and treating victims of trafficking [22,23]. Progress has been made, however, in developing and disseminating recommended practices and protocols in institutions [24].…”
Section: Building Practice-policy Feedback Loopsmentioning
confidence: 99%